Implikatur Wacana Humor dalam Webtoon â€œTahi Lalatsâ€ Karya Nurfadli Mursyid - Sri Juniati (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
The formulation of the problem in this study is (1) What is the meaning of implicature in humorous discourse webtoon "Tahi Lalats" by Nurfadli Mursyid? (2) What is the manifestation of the violation of the principle of cooperation found in humorous discourse webtoon "Tahi Lalats" by Nurfadli Mursyid. The objectives of this study are (1) To describe the intent of implicature in humorous discourse "Tahi Lalats" webtoon by Nurfadli Mursyid, (2) Describe the form of violations of the principle of cooperation found in humorous discourse "Tahi Lalats" by Nurfadli Mursyid. This research method is descriptive qualitative research. The data source of this research is the humorous discourse on the Taht Lalats webtoon edition January-March 2018. While the research data is in the form of sentences that are indicated to contain implicatures and violate the principle of cooperation in humor discourse in the Tahi Lalats webtoon. Based on the two formulations of the above problem, the conclusions from this study are (1) the researchers found seven implicature purposes, namely: telling, criticizing, accepting, rejecting, threatening, challenging, and threatening. (2) the researcher found violations of the principle of cooperation which violated four maxims, namely: maxim of quantity, maxim of quality, maxim of relevance and maxim of implementation. Keywords: Implicature, Discourse, Principle of Cooperation